Governing Medical Knowledge Commons - Strandburg, Katherine J.; Frischmann, Brett M.; Madison, Michael J. (Social Sciences, 2017)
This book supplies evidence that policymakers, researchers, and designers need to develop strategies for producing better innovation and systems of information production. The book's knowledge commons concept offers a systematic way of understanding institutions for knowledge sharing, with fifteen new case studies in the medical and health sciences context. The book is also available as Open Access.